Pelanggaran Ham Yang Terjadi Di Papua Dan Poso - Rustandi Senjaya (Fakultas Syariah UIN Antasari, 2022)
Abstract: The purpose of this study is to demonstrate if the legal commission has to be familiar with the fundamentals of human rights in an international setting. The strategy used in this study incorporates normative works that analyze human rights breaches in Papua and Poso from a variety of journal sources. Based on these instances, the study concludes that special measures are required in order to lessen law enforcement's infringement of human rights. For legal certainty and tangible references by all parties, the framework for international and national regulation is required. Law enforcement organizations must put in place a UN system that can quickly react to requests from States for human rights education and training initiatives, special education on standards as set out in international human rights instruments and in humanitarian law and their application to special groups such as law enforcement personnel.Â Abstrak: Penelitian ini ingin membuktikan apakah komisi hukum perlu memahami dasar HAM dalam konteks internasional. Metode dalam penelitian ini menggunakan kajian normative dari berbagai referensi jurnal yang membahas tentang pelanggaran HAM di Papua dan Poso. Penelitian ini menemukan bahwa diperlukan pengaturan khusus berdasarkan kasus-kasus tersebut agar pelanggaran HAM oleh penegak hukum dapat berkurang. Dasar pengaturan baik secara internasional dan nasional diperlukan demi kepastian hukum dan acuan yang konkret oleh semua pihak. Lembaga-lembaga penegak hukum harus menerapkan system PBB yang dapat segera merespon permintaan dari Negara untuk kegiatan pendidikan dan pelatihan di bidang HAM pendidikan khusus tentang standar sebagaimana tercantum dalam instrumen HAM internasional dan dalam hukum humaniter dan penerapannya pada kelompok-kelompok khusus seperti personel penegak hukum.